LA PUBLICIDAD TELEVISIVA DIRIGIDA A MENORES EN ESPAÑA: SEGUIMIENTO DEL CÓDIGO PAOS - Gdo. David RAMÍREZ PONCE,Dra. María Cruz LÓPEZ DE AYALA (Fonseca, Journal of Communication, 2023)
In a context of concern about the high prevalence of obesity among Spanish children, the debate on television advertising of food and drink products to children becomes more important. Although there are other factors that influence childhood obesity, there is evidence that commercial have a great impact on the eating habits of children